Evaluation of Early Corticosteroid Therapy in Management of Pediatric Septic Shock in Pediatric Intensive Care Patients: A Randomized Clinical Study. Issue 2 (February 2017) - El-Nawawy, Ahmed; Khater, Doaa; Omar, Heba; Wali, Yasser
Abstract : Background: Septic shock is a major healthcare problem. Adrenal insufficiency (AI) in children with septic shock is a recognized complication, yet is controversial regarding its management and effect on mortality. According to the current guidelines, children with risk factors for AI should receive a stress dose of steroids in step 3 of treatment. This study aimed to evaluate and compare early corticosteroid therapy with the traditional use of steroids among pediatric septic shock patients. Methods: This prospective randomized interventional clinical study included 3 groups of patients (32 each) and was conducted in Alexandria University pediatric intensive care unit. By protocol, the first group received steroids in step 3 of the treatment according to the current international guidelines (group A), and the second group was managed as group A and was tested for AI by adrenal stimulation test using intramuscular adrenocorticotropic hormone (cosyntropin) (group B). The third group received steroids at the start of fluid therapy (group C). A fourth group (group D) was created by adding patients from groups A and B who needed corticosteroids in the third stage of therapy according to the international protocol in 1 group. All patients were evaluated for basal serum cortisol and plasma adrenocorticotropic hormone concentrations. Results: The data showed a statistically significant shorter shock reversal time among patients receiving corticosteroids at the start of treatment compared with those who received it at the third step of treatment ( P = 0.046); however, mortality was not statistically different among the groups. In addition, there was no superinfection in cases receiving early steroid therapy. Conclusions: Early use of corticosteroid in patients with septic shock might shorten the shock reversal time without increase in mortality or superinfection. Abstract : Supplemental Digital Content is available in the text.